Nonfinancial Firms in Latin America : A Source of Vulnerability? - Gonzalez, Maria (IMF Working Papers; Working Paper, 2012)
We examine corporate sector vulnerabilities in Brazil, Chile, Colombia, Mexico and Peru. First, we identify stylized facts based on corporate financial indicators. Second, we assess vulnerability of individual firms to a sudden stop in financing through a probit model, using a panel of 18 countries in 2000-11. Results suggest that higher leverage and maturity exposures raise a firm's probability to become exposed to a funding shock, while a larger firm size and buffers reduce it. Further, greater exchange rate flexibility can help mitigate corporate vulnerability. Identification of firms at risk through the model suggests that some vulnerabilities may be building in Latin America led by leverage, currency exposures and moderating buffers. These effects are partially offset, however, by a significant reduction in maturity exposures.